Structural Analysis of the Equation Model on Store Atmosphere towards Hedonic Value and Consumer Impulsive Buying (Study at Majapahit Food Center) - Rini Anggriani; Anthony Anggrawan; Irwan Cahyadi (Jurnal Varian, 2020)
This study aims to determine the analysis of Structural Equation Modeling (SEM) of store atmosphere on Hedonic Value and Impulsive Buying of Consumers at the Majapahit Food Center. This type of research uses causality research with a sample of respondents who are consumers who visited at Majapahit Food Center Mataram. The sampling technique used the accidental sampling technique. The study population was 100 visitors to the Majapahit Food Center. Sampling using the accidental sampling technique. The data collection technique used a questionnaire with a Likert scale measuring instrument. The data analysis method used is a validity test, reliability test, using SPSS, and data analysis using Structural Equation Modeling (SEM) with AMOS. The results of the study stated that the store atmosphere has a positive and significant effect on Hedonic Value and the Store Atmosphere has a positive and significant effect on Impulsive Buying and Hedonic Value has a positive and significant effect on Impulsive Buying Consumers in the Majapahit Food Center Study.